Comparative study of the immunoprotective effect of two DNA vaccines against grass carp reovirus. Issue 75 (April 2018) - Chen, Dan-Dan; Yao, Yuan-Yuan; Cui, Zheng-Wei; Zhang, Xiang-Yang; Peng, Kai-Song; Guo, Xia; Wang, Biao; Zhou, Yuan-Yuan; Li, Shun; Wu, Nan; Zhang, Yong-An
Abstract: Grass carp reovirus II (GCRV II) causes severe hemorrhagic disease with high mortality in grass carp, Cyenopharyngodon idellus . DNA vaccination has been proven to be a very effective method in conferring protection against fish viruses. However, DNA vaccines for GCRV II have not yet been conducted on grass carp. In the current work, we vaccinated grass carp with a DNA vaccine consisting of the segment 6 (pC-S6; encoding VP4) or 10 (pC-S10; encoding NS38) of GCRV II and comparatively analyzed the immune responses induced by these two vaccines. The protective efficacy of pC-S6 and pC-S10, in terms of relative percentage survival (RPS), was 59.9% and 23.1% respectively. This suggests that pC-S6 and pC-S10 DNA vaccines could increase the survival rate of grass carp against GCRV, albeit with variations in immunoprotective effect. Immunological analyses indicated the following. First, post-vaccination (pv), both pC-S6 and pC-S10 up-regulated the expression of interferon (IFN-1), Mx1, IL-1β, and TNF-α. However, CD4 and CD8α were up-regulated in the case of pC-S6 but not pC-S10. Second, comparing non-vaccinated and pC-S10-vaccinated fish, the T cell response related genes, such as CD4, CD8α, and GATA3, were elevated in pC-S6-vaccinated fish at 48 h post-challenge (pc). Third, pC-S6 and pC-S10 induced similar patterns of specific antibody response pv. However, only anti-VP4 IgM in the sera of surviving fish infected with GCRV was significantly increased pc compared with that pre-challenge. Taken together, these results indicate that pC-S6 promotes both innate (IFN-1 and Mx1 induction) and adaptive (T cell and specific antibody response) immunity pv and that the induction of a memory state promptly primes the immune response upon later encounters with the virus, whereas pC-S10 only induces the type I IFN-related response pv and a lower inflammatory response pc. Highlights: DNA vaccine pC-S6 induced higher immunoprotective effect of grass carp against GCRV II than pC-S10. Immnoprotective effects of pC-S6 and pC-S10 varied due to different immune responses induced by them. pC-S6 promoted both innate and adaptive immunity post-vaccination. Post-challenge, a memory state was promptly primed in pC-S6-immunized fish.